Preliminary report: one of the PD-1 gene variants may be a valuable marker for colorectal cancer - Lamami, Yosra; Mesediyeva, Roya; Arikan, Soykan; Ercan, Şeyda; Kıyan, Hilal Fındık; Tatar, Cihat; Nayci, Ali Emre; Farooqi, Ammad; Yaylim, İlhan; Kiran, Bayram (Termedia Sp. z.o.o., 2018)
IntroductionIntroduction: Programmed death-1 (PD-1), an important immunosuppressive molecule, plays a key role in tumor-cell-mediated immune escape. The present study aimed to investigate the role of PD-1.5 (C/T) gene polymorphisms on the susceptibility and progression of colorectal cancer (CRC).Material and methodsIn this study, the PD-1.5 C/T polymorphism was investigated in 99 CRC patients and 150 healthy individuals as controls by nested polymerase chain reaction-restriction fragment length polymorphism methodResultsThe distributions of PD-1.5 (C/T) genotypes and alleles were in agreement with Hardy–Weinberg equilibrium in controls (p>0.05) but not in CRC patients (p=0.02). We found a statistical significance difference between CRC patients and controls for the genotypic distribution of PD-1.5(C/T) genotypes (p=0.003) and also for alleles (p=0.004). The patients who have T allele have increased according to the controls (p=0.001). The patients who have C allele with distance metastasis have increased heterozygous CT genotype of PD-1.5 (C/T) polymorphism than those with no metastasis (p<0.001). We also detected the increased CC genotype in patients who have angiolymphatic invasion (p=0.043). The patients who have mucineous component have increased frequency of T allele than those with the absence of mucineous component (p=0.023).ConclusionsOur results have shown significant associations between PD-1.5 genotypes and CRC susceptibility and progression of the disease.
Keywords: 3. Good health